Cursed Sequential Equilibrium - Fong, Meng-Jhang; Lin, Po-Hsuan; Palfrey, Thomas R. (American Economic Review, 2025)
This paper develops a framework to extend the strategic form analysis of cursed equilibrium (CE) developed by Eyster and Rabin (2005) to multistage games. The approach uses behavioral strategies rather than normal form mixed strategies and imposes sequential rationality. We define and characterize properties of cursed sequential equilibrium (CSE) and apply it to four canonical economic applications: signaling games, reputation building, durable goods monopoly, and the dirty faces game. These applications illustrate various implications of CSE, show how and why it differs from sequential equilibrium and CE, and provide evidence from laboratory experiments that support the empirical relevance of CSE. (JEL C72, C73, D42, D82, D83)